Synthesis and evaluation of 4,4 ',6,6 '-tetrasubstituted binaphtholphosphate dirhodium(II) complexes as catalysts in enantioselective carbonyl ylide formation-cycloaddition reactions - Hodgson, D; Selden, D; Dossetter, A (2003)
The synthesis of tetrakis[4,4′,6,6′-tetrasubstituted-1, 1′-bi-2-naphtholphosphate]dirhodium(II) complexes, and their use as catalysts in the enantioselective tandem carbonyl ylide formation- intramolecular 1,3-dipolar cycloaddition of an unsaturated 2-diazo-3,6- diketoester, generating cycloadduct in up to 86% ee, is described. © 2003 Elsevier Ltd. All rights reserved.